Research and realisation of real-time Ethernet protocol for networked motion control system. (15th November 2019) - Feng, Shouting; Zhuo, Zhongshuo; Pan, Daru
Existing control cards typically use non-real-time Ethernet protocols, such as TCP/IP, making it difficult to achieve multi-axis synchronisation between control cards. A practical scheme is proposed in this paper to solve this problem. In this scheme, the internal clocks of control cards are adjusted to the same value by the sync frames periodically sent by the host. The jitter of the sync frame has very little impact on the consistency of the clocks of all control cards. This alleviates the real-time performance requirements of the host, and thus reduces the cost and design difficulty. In addition, all synchronous or asynchronous frames are unified into a cluster frame model, which simplifies the processing of the frames, making it easy to implement in hardware such as FPGAs. This real-time Ethernet protocol has been implemented in a large-scale motion control chip. And the test results showed that this scheme achieves expected performance.